Vitamin C - Hamza, Amal H. (IntechOpen, 2017)
This book highlights recent advances on vitamin C and related topics. The chapters of this book include basic information about vitamin C function, sources and analysis, and radioprotective and antioxidant effect of vitamin C. Also, the anticarcinogenic effect of vitamin C is introduced. Furthermore, we considered the encapsulation technique used in vitamin C preparation. Finally, recent advances in vitamin C transporter are illustrated.